Stability in student well-being and educational disparities across the pandemic: a latent profile analysis of PISA 2018 and 2022 in Finland, Sweden, and Iceland ... - Repo, Juuso; Reimer, David; Kilpi-Jakonen, Elina (figshare, 2025)
Abstract This study examined changes in student well-being and its relationship with academic performance, in light of concerns about rising inequalities caused by the COVID-19 pandemic. It utilized PISA student surveys and reading and math assessments from 2018 and 2022 (N = 33,147) among 15-year-old adolescents from Finland, Sweden, and Iceland. Adopting a person-centred approach, the study aimed to identify distinct well-being profiles based on their school attendance, life satisfaction, and sense of school belonging. Four well-being profiles were identified in both cohorts: High Well-being, Moderate Well-being, Present but Disconnected, and Disengaged. Unexpectedly, the proportions of students within each profile remained stable over time. Lower socioeconomic status (SES) was consistently associated with less favourable well-being profiles, though the interaction between SES and cohort was not significant, indicating persistent but not worsening disparities. Academic performance declined across all ...